2022
DOI: 10.3390/cancers14184434
|View full text |Cite
|
Sign up to set email alerts
|

Scalloping of the Liver and Spleen on Preoperative CT-Scan of Pseudomyxoma Peritonei Patients: Impact on Prediction of Resectability, Grade, Morbidity and Survival

Abstract: Pseudomyxoma peritonei (PMP) is ideally treated by cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC), leading to significant morbidity. Beyond the histologic grade, the prognosis lies in the completeness of cytoreduction (CC-score of 0/1 vs. 2/3) and the severe complication rate. The mucinous nature of the peritoneal implants sometimes induces liver and/or spleen scalloping on imaging. The predictive value of scalloping was assessed regarding resectability, grade, survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Contrast-enhanced CT and MRI imaging are useful in confirming the nature of the tumor and ascites, and predicting the presence of distant metastases, peritoneal dissemination, and lymph node enlargement, as well as the staging of the ovarian tumor. In addition, findings of appendiceal mucocele or the findings of liver or spleen serosal surface compression due to myxoma seeding (scalloping sign), although not seen in our cases, may also be useful as a preoperative diagnosis for PMP 16 - 18) .…”
Section: Discussionmentioning
confidence: 59%
“…Contrast-enhanced CT and MRI imaging are useful in confirming the nature of the tumor and ascites, and predicting the presence of distant metastases, peritoneal dissemination, and lymph node enlargement, as well as the staging of the ovarian tumor. In addition, findings of appendiceal mucocele or the findings of liver or spleen serosal surface compression due to myxoma seeding (scalloping sign), although not seen in our cases, may also be useful as a preoperative diagnosis for PMP 16 - 18) .…”
Section: Discussionmentioning
confidence: 59%
“…9 Liver scalloping, a radiologic sign made by the mass effect of the mucinous neoplasm against the liver and other viscera, is pathognomonic for PMP. 1,2,[4][5][6][7]10 In a retrospective study of 159 patients with PMP, Hotta et al 6 found that visceral scalloping on CT scans correlated with cancer recurrence after CRS. Identifying patients at risk of recurrence is crucial for selecting the appropriate treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Cytoreductive surgery and HIPEC are not without limitations and complications. Complete CRS may require extensive resections of the greater omentum or visceral peritoneum, which can lead to increased complications, decreased quality of life, 2 ileus, fistulas, gastroparesis, and abscesses. 4 Appendectomy is indicated even if the appendix appears normal or the tumor is of ovarian origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations